PEMBATASAN MASA JABATAN KETUA UMUM PARTAI POLITIK: TINJAUAN NEGARA HUKUM DAN DEMOKRASI - Ghafur, Jamaludin (LITIGASI, 2024)
This paper aims to identify the implications of not regulating the term limits of political party chairmen on the principles of the rule of law and democracy and to find juridical and conceptual reasons for the government to regulate it. This research employs a normative legal method with a statutory and conceptual approach. Some of the research findings show that the implications of the absence of rules limiting the term of office of political party chairmen have negative implications for the principles of the rule of law and democracy, namely that leadership turnover or regeneration does not take place regularly. As a result, the majority of leadership in political parties has an authoritarian character where the party as an organization is not managed based on rules, but is determined by the authority and personal subjectivity of the chairperson. Initially, the limitation on the term of office of party chairpersons was not included in the regulation to prevent the Government from interfering in the internal affairs of parties, which based on past experience - especially during the Old Order and New Order, excessive state intervention has led to violations of citizens' constitutional rights to associate and assemble. Currently, the threat to citizens' freedom of association and assembly comes from the internal power of political parties, particularly from party chairpersons. With enormous and almost unlimited authority, party chairmen can act arbitrarily. Therefore, it is time for the Government to strictly regulate the limitation of the term of office of party chairpersons to...